2013
DOI: 10.1371/journal.pone.0073619
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Bird Communities to Farmland Abandonment in a Mountain Landscape

Abstract: Widespread farmland abandonment has led to significant landscape transformations of many European mountain areas. These semi-natural multi-habitat landscapes are important reservoirs of biodiversity and their abandonment has important conservation implications. In multi-habitat landscapes the adaptation of communities depends on the differential affinity of the species to the available habitats. We use nested species-area relationships (SAR) to model species richness patterns of bird communities across scales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Recent studies have presented rewilding as an alternative option for land use in cases of farmland abandonment (Guilherme and Pereira 2013;Navarro and Pereira 2012;Queiroz 2013). The trends in land abandonment could also be seen as an opportunity rather than a threat, even though the conservation of traditional farming systems is also associated with biodiversity and cultural value (Navarro and Pereira 2012).…”
Section: Strengths and Weaknesses Of Rewilding: Implications For Consmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have presented rewilding as an alternative option for land use in cases of farmland abandonment (Guilherme and Pereira 2013;Navarro and Pereira 2012;Queiroz 2013). The trends in land abandonment could also be seen as an opportunity rather than a threat, even though the conservation of traditional farming systems is also associated with biodiversity and cultural value (Navarro and Pereira 2012).…”
Section: Strengths and Weaknesses Of Rewilding: Implications For Consmentioning
confidence: 99%
“…Several authors have recently suggested that rewilding 1 may be an appealing conservation response to farmland abandonment in areas of Europe and the rest of the world where the social structure of farming communities has been eroded and low-intensity farming is no longer socially or economically viable (Navarro and Pereira 2012;Guilherme and Pereira 2013;Queiroz et al 2014). These authors propose rewilding as a potential alternative approach to conservation, in which the maintenance costs are much lower than the current target-driven, intensively managed approaches (Gillson et al 2011;Navarro and Pereira 2012;Queiroz et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species diversity patterns in traditional landscapes are likely to be different from what would be found in non-modified (primary) landscapes (Blondel and Aronson 1999). When the total number of species is considered, a higher richness of species at the habitat patch scale (i.e., α-diversity) is expected in traditional landscapes due to species being able to use more than one habitat and due to the high density of habitat edg-es, which facilitates inter-patch movements and therefore leads to a higher species turnover in space and time (Proença and Pereira 2013;Guilherme and Pereira 2013). Note that even with inter-patch movements, each habitat type will support a distinct community of species due to differences in species abundances and due to the existence of strict habitat specialists.…”
Section: Disturbances and Diversitymentioning
confidence: 99%
“…As much as 60% of bird species with various ecosystem role lives on the agroforestry area [9]. Moreover, there is an interesting tendency in which the birds prefer to live on the transition region between farmland and primary forest as illustrated by agroforestry, compared to other area, such as monoculture forest and active farmland [10,11].…”
Section: Introduction *mentioning
confidence: 99%